The Piping Failure Mechanism of a Loess Dam: The 2021 Dam Break of the Yang Village Reservoir in China - Ma, Wenguo; Zhang, Gang; Yang, Youzhen; Wang, Ping; Zhao, Yishen; Lin, Qingqing (Frontiers in Earth Science, 2022)
The construction of a reservoir on a large-thickness collapsible loess cover will significantly increase the occurrence of dam break disasters. The main reason may be that although the gradation of loess particle is not uniform. The clay content is less than 10%. Piping channels are easy to form under the action of force and collapsibility. Near-static liquefaction of the loess in the dam body under the saturated condition will lead to the piping or loss of soil strength. Therefore, it is of great significance to study the mechanical characteristics of loess in the saturated state for preventing dam break. The study investigated the 2021 dam failure of the Yang Village Reservoir in Ningxia, China, which resulted in millions of dollars in property damage but no casualties. The dam break is a gradual development from the piping to complete dam break. This study tries to find out the real reason for dam-break from the physical and mechanical properties of the foundation and the dam. Mainly carried out the research through the following three aspects: First, the dam structure identified by using the seismograph, the compactness of the dam foundation and the dam body determined according to the wave velocity of the soil layer, and the construction quality of the dam foundation and the dam body comprehensively evaluated. Secondly, the particle size distribution confirmed the mechanism of uneven particle size distribution and clay loss. Finally, the undrained characteristics of saturated loess are tested, and the dam failure is essentially explained. The research results show that using this loess to fill the dam foundation directly and the dam body has a very high probability of piping-type dam failure. This paper gives some design suggestions for using this loess for dam building, for example, through the design of the filter layer to increase the difficulty of piping occurrence.